2020
DOI: 10.1088/1748-605x/ab673b
|View full text |Cite|
|
Sign up to set email alerts
|

Single-step, acid-based fabrication of homogeneous gelatin-polycaprolactone fibrillar scaffolds intended for skin tissue engineering

Abstract: Blends of natural and synthetic polymers have recently attracted great attention as scaffolds for tissue engineering applications due to their favorable biological and mechanical properties. Nevertheless, phase-separation of blend components is an important challenge facing the development of electrospun homogeneous fibrillar natural-synthetic polymers scaffolds; phase-separation can produce significant detrimental effects for scaffolds fabricated by electrospinning. In the present study, blends of gelatin (Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
4
16
0
Order By: Relevance
“…In the current study, fibrillar membranes of PCL and Gel loaded with different amounts of ZnO-NPs were fabricated by the electrospinning technique using AcAc. Worth mentioning that AcAc is considered a "green" solvent, since it is less toxic than other solvents, such as hexafluoro-2-propanol (HFP) or trifluoroethanol (TFE), frequently used for miscible Gel-PCL electrospinning solutions [32,43]. As a consequence of the synthesis conditions, hydrogen bonds between PCL and Gel were exhibited by the FTIR, this hydrogen bonding influenced the A c c e p t e d M a n u s c r i p t structural and mechanical properties of the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, fibrillar membranes of PCL and Gel loaded with different amounts of ZnO-NPs were fabricated by the electrospinning technique using AcAc. Worth mentioning that AcAc is considered a "green" solvent, since it is less toxic than other solvents, such as hexafluoro-2-propanol (HFP) or trifluoroethanol (TFE), frequently used for miscible Gel-PCL electrospinning solutions [32,43]. As a consequence of the synthesis conditions, hydrogen bonds between PCL and Gel were exhibited by the FTIR, this hydrogen bonding influenced the A c c e p t e d M a n u s c r i p t structural and mechanical properties of the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the CA layer, the resulting contact angle suggests hydrophobic characteristics [ 32 ]. The scaffold physical properties could assist in cell migration and differentiation [ 33 ], according to previously reported results where the lower the contact angle of the material, the greater the hydrophilicity and the higher the biocompatibility [ 34 ]. Considering these results, the potential application of this material as a dressing for wounds exists, given that the layer that would be in direct contact with the tissue would be the PG+gen and the CA layer could fulfill the role as physical barrier to avoid colonization by microorganisms [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors indicated that surface of PLGA/collagen/graphene oxide scaffold was more beneficial for skeletal myoblast adhesion, proliferation, and differentiation in comparison with surface of PLGA/graphene oxide biomaterial. In turn, Prado-Prone et al [163] proved that contact angle decreased, when the content of gelatin in PCL scaffold increased. Thus, the contact angles of PCL, PCL/30 wt.% gelatin, and PCL/45 wt.% gelatin biomaterials were approximately 127 • , 65 • , and 25 • , respectively.…”
Section: Surface Wettabilitymentioning
confidence: 98%
“…Moreover, unlike hydrophobic surfaces, the hydrophilic ones maintain proper conformation of adsorbed proteins, which promotes cell adhesion and proliferation [21,138,158,167,168]. Unfortunately, the above-mentioned papers [140,[160][161][162][163][164][165][166] do not present experiments that evaluate biomaterial ability to adsorb proteins from surrounding liquids. In turn, Lü et al [169] fabricated chitosan/collagen film and demonstrated that its surface was more hydrophilic (θ = 64 • ) compared to surface of chitosan biomaterial (θ = 86 • ).…”
Section: Surface Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation